2015
DOI: 10.1007/s00122-015-2581-2
|View full text |Cite
|
Sign up to set email alerts
|

Genetic architecture of maize kernel row number and whole genome prediction

Abstract: Key messageMaize kernel row number might be dominated by a set of large additive or partially dominant loci and several small dominant loci and can be accurately predicted by fewer than 300 top KRN-associated SNPs.AbstractKernel row number (KRN) is an important yield component in maize and directly affects grain yield. In this study, we combined linkage and association mapping to uncover the genetic architecture of maize KRN and to evaluate the phenotypic predictability using these detected loci. A genome-wide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
44
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(60 citation statements)
references
References 47 publications
(81 reference statements)
10
44
0
Order By: Relevance
“…Natural variation in the CLV-WUS pathway underlies yield improvements in different crop species including tomato, maize and mustard (Bommert et al 2013b;Fan et al 2014;Xu et al 2015;Je et al 2016), and FEA2 is a quantitative trait locus (QTL) for kernel row number (KRN) (Bommert et al 2013b). In this study, we used a maize association panel of 368 diverse inbred lines to show that ZmCRN also has significant association with KRN under multiple environments Liu et al 2015), suggesting that ZmCRN contributes to quantitative variation in this trait. Therefore, ZmCRN could be manipulated for maize yield enhancement.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Natural variation in the CLV-WUS pathway underlies yield improvements in different crop species including tomato, maize and mustard (Bommert et al 2013b;Fan et al 2014;Xu et al 2015;Je et al 2016), and FEA2 is a quantitative trait locus (QTL) for kernel row number (KRN) (Bommert et al 2013b). In this study, we used a maize association panel of 368 diverse inbred lines to show that ZmCRN also has significant association with KRN under multiple environments Liu et al 2015), suggesting that ZmCRN contributes to quantitative variation in this trait. Therefore, ZmCRN could be manipulated for maize yield enhancement.…”
Section: Discussionmentioning
confidence: 95%
“…The maize crn (Zmcrn) mutants had larger vegetative to ask if it is also associated with this yield trait. We conducted a candidate gene association study using a maize association panel of 368 diverse inbred lines Liu et al 2015). We found that three SNPs in the 3'UTR region of CRN showed significant association with KRN in multiple environments, below the threshold P-value < 0.001 (Figure supplement 4 and Table supplement 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous simulations or empirical studies of prediction, the GS model has consistently outperformed an MAS model as it captured the genetic variance of a trait over the entire genome rather than a few significant markers (Jiang et al, 2017; Liu et al, 2015). In a cross‐validation study, the prediction accuracy of GS in the association population was consistently higher than that of the MAS model.…”
Section: Discussionmentioning
confidence: 95%
“…Numerous quantitative trait locus (QTL) studies for yield‐related traits in maize were conducted by linkage mapping (Martinez et al, ; Pan et al, ) and association mapping (Liu et al, ; Millet et al, ; Xiao et al, ). These studies used many different populations, including F 2:3 (Guo et al, ), BC 2 F 2 (Li, Zhang, Li, Wang, & Zhou, ), recombinant inbred lines (RILs; Liu et al, ; Pan et al, ), IF 2 (immortalized F 2 ; Tang et al, ), IAP (inbred association panel; Liu et al, ), MAGIC (multi‐parent advanced generation intercross population (Dell’Acqua et al, ) and ROAM (random‐open‐parent association mapping; Xiao et al, ) and reported numerous QTLs and significant single‐nucleotide polymorphisms (SNPs) associated with grain yield‐related traits. Earlier studies (Gonzalo, Holland, Vyn, & McIntyre, ; Gonzalo, Vyn, Holland, & McIntyre, ; Guo et al, ) to map QTLs for grain yield were evaluated under different planting densities, though little attention has been paid to QTLs for grain yield relative to density tolerance.…”
Section: Introductionmentioning
confidence: 99%